A Globalized Market--Opportunities and Risks for the Poor : Global Poverty Report 2001 - African Development Bank; Asian Development Bank; European Bank for Reconstruction and Development; Inter-American Development Bank; International Monetary Fund; World Bank (World Bank, Washington, DC, 2014)
The Global Poverty Report considers the effects of globalizing markets on poverty in developing countries. It outlines the channels through which increased trade openness can affect poverty and examines the evidence from four regions: Sub-Saharan Africa, Asia and the Pacific, Eastern Europe and Central Asia, and Latin America and the Caribbean. Written at the request of the G8, the report is the result of a joint effort of the regional development banks, the World Bank, and the International Monetary Fund. Increased openness can affect an economy in various ways, creating opportunities for the poor as well as risks. First, it can affect the prices of goods and services that the poor consume and produce, benefiting those who are net consumers of goods that become cheaper and those who can obtain higher prices for their products on international markets. Second, it can affect the demand for and returns to factors of production that the poor have to offer, such as labor. Third, it can affect government revenue and the resources available for antipoverty programs. Fourth, it can influence the potential for economic growth, which in turn affects poverty. Fifth, the short-term costs of transition, as well as the possible increased volatility of growth stemming from the opening up of markets, may increase the need for social protection mechanisms. Comprehensive trade reform can help reduce poverty when it is part of a set of reforms that improve the domestic macroeconomic and investment climate, enhance infrastructure and technology, and contribute to the provision of knowledge and skills. However, these effects vary significantly across countries, regions, and groups within countries, which makes it difficult to generalize about the effects of trade liberalization on poverty.